Comorbid Tourette's and Bipolar Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Of 205 patients with Tourette's disorder in the North Dakota Longitudinal Tourette Syndrome Surveillance Project, 15 had comorbid bipolar disorder.